Dr. Luigi (Gigi) Varesio: A memorial. Issue 6 (1st April 2018) - Young, Howard; Blasi, Elisabetta; Cox, George; Carla Bosco, Maria
Abstract : Memorial tribute to Dr. Varesio's career and contributions to the field of leukocyte biology.